Cefminox, a Dual Agonist of Prostacyclin Receptor and Peroxisome Proliferator-Activated Receptor-Gamma Identified by Virtual Screening, Has Therapeutic Efficacy against Hypoxia-Induced Pulmonary Hypertension in Rats - Xia, Jingwen; Yang, Li; Dong, Liang; Niu, Mengjie; Zhang, Shengli; Yang, Zhiwei; Wumaier, Gulinuer; Li, Ying; Wei, Xiaomin; Gong, Yi; Zhu, Ning; Li, Shengqing (Frontiers in Pharmacology, 2018)
Prostacyclin receptor (IP) and peroxisome proliferator-activated receptor-gamma (PPARγ) are both potential targets for treatment of pulmonary arterial hypertension (PAH). Expression of IP and PPARγ decreases in PAH, suggesting that screening of dual agonists of IP and PPARγ might be an efficient method for drug discovery. Virtual screening of potential IP–PPARγ dual-targeting agonists was performed in the ZINC database. Ten of the identified compounds were further screened, and cefminox was found to dramatically inhibit growth of PASMCs with no obvious cytotoxicity. Growth inhibition by cefminox was partially reversed by both the IP antagonist RO113842 and the PPARγ antagonist GW9662. Investigation of the underlying mechanisms of action demonstrated that cefminox inhibits the protein kinase B (Akt)/mammalian target of rapamycin (mTOR) signaling pathway through up-regulation of the expression of phosphatase and tensin homolog (PTEN, which is inhibited by GW9662), and enhances cyclic adenosine monophosphate (cAMP) production in PASMCs (which is inhibited by RO113842). In a rat model of hypoxia-induced pulmonary hypertension, cefminox displayed therapeutic efficacy not inferior to that of the prostacyclin analog iloprost or the PPARγ agonist rosiglitazone. Our results identified cefminox as a dual agonist of IP and PPARγ that significantly inhibits PASMC proliferation by up-regulation of PTEN and cAMP, suggesting that it has potential for treatment of PAH.